Advances in Nutritional Interventions for Patients with Diabetes Mellitus - Weng, Lurui (International Journal of Public Health and Medical Research, 2025)
With the accelerated aging process in China, there are more and more diabetic patients, especially the elderly. The function of pancreatic β-cells in the elderly body gradually declines, insulin secretion ability decreases, and blood glucose regulation ability is weakened. In addition, the body's tolerance to glucose decreases, easily triggering diabetes. The high prevalence of diabetes mellitus and the high number of risk factors make it easy to cause various complications. Based on this situation, in recent years, the research on the treatment and care of diabetic patients has also made good progress, basically favoring nutritional intervention, which is more effective and less likely to induce adverse reactions, and is a more popular intervention. Therefore, this paper will synthesize the research results of scholars at home and abroad, discuss and analyze the research progress of nutritional intervention in diabetes mellitus patients, and provide certain references and reference for the dietary care of diabetes mellitus patients in the future.